(untitled) (PerCursos, 2024)
This article is a constituent part of the Master’s Dissertation defended within the scope of the Postgraduate Program in Social Service/UFPA, which aimed to carry out an analysis of academic productions (dissertations and theses) published in the period from 2012 to 2022, which dealt with the theme housing, with the main focus being housing programs, especially “Minha Casa, Minha Vida” (PMCMV). This bibliographical research demonstrated that the residents of these projects seek to preserve the use value of the house and the fact of not returning to live in camps and occupations; and that the right to live, built in the daily life of poverty, expresses the way of living and being of these families; that residential families live with the low infrastructure and architectural quality of the housing units and the difficult location of the projects. To achieve these results, surveys in the CAPES catalog were used as methodological procedures, followed by analysis of speeches in dialogue with the referenced authors, especially the classic thinkers of dialectical historical materialism.